(3cJGH EjVGM GdeTcd ef GdebQHs - (3CHh GdMSf Ydj Hf eDef GdETHjdi GdMVQei GdeYQha HGHf YUahQs; (3CHh GdMSf Ydj Hf eDef Hf YUahQ GdGTHjdjs
(3ChdgG (B:s
(3GdMeO ddg HGQi GdfSe heGfM GdbSe GdeJWhd Ydi GdEfSGf HGddSGf hGdeejR dg Yf SGFQ GdMjhGf hHYO aEfi deG SdcJ ai cJGHi GdeSei HGdebQH eSdc GdGNJUGQ PcQ MbjbI GdfMh s
(3BNQgG (B:s
(3hCeG JLhjOge Pdc ajg YfO GdEVWQGQ aYdjg CcKQ GdVQGjQ JeJ HMeO Gddg hYhfg hMSf Jhajbg hGdUdGI Ydi NjQ Ndbg eMeO fHjg hYdi Bdg hUMHg hSde JSdjekG cKjQkG Edi jhe GdOjf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs